Concurrent Diabetes Mellitus may Negatively Influence Clinical Progression and Response to Androgen Deprivation Therapy in Patients with Advanced Prostate Cancer - Shevach, Jeffrey; Gallagher, Emily Jane; Kochukoshy, Teena; Gresia, Victoria; Brar, Manpreet; Galsky, Matthew D.; Oh, William K. (Frontiers in Oncology, 2015)
Objective: To determine if a concurrent diagnosis of diabetes mellitus is associated with worse outcomes in advanced prostate cancer. The effect diabetes may have on the progression of advanced prostate cancer is poorly understood. Methods: Data on 148 advanced prostate cancer patients (35 with concurrent diabetes) were collected from an institutional database to obtain diabetic status, data on treatment types and durations, and PSA values before, during and after treatment. Time to castration resistance following the onset of androgen deprivation therapy (ADT) and overall survival in patients with and without diabetes were compared using univariate Cox regression analyses as the primary endpoints. Differences in PSA response to treatments were compared using chi-squared tests as a secondary endpoint. Results: With a median follow-up of 29 months, time to castration resistance did not differ significantly between patients with and without diabetes who underwent ADT. However, in a subset of patients who received ADT without radiographic evidence of metastases (N=47), those with diabetes progressed to castration-resistant disease more quickly than those without diabetes (Hazard Ratio for progression with diabetes = 4.58; 95% CI: 1.92-10.94; p = 0.0006). Also, a lower percentage of patients with diabetes undergoing ADT had PSA declines of at least 50% (p=0.17) and reached a nadir PSA <0.2 ng/mL (p=0.06). Overall survival did not differ based on diabetic status. No differences were seen in response to first-line therapy for castration-resistant prostate cancer. Conclusions: Diabetes mellitus may have a detrimental effect on progression of advanced prostate cancer, particularly in those patients without radiographic evidence of metastases. Further study is necessary to fully elucidate the effect of diabetes on prostate cancer outcomes.